Crisis management during anaesthesia: cardiac arrest. Issue 3 (2nd June 2005) - Runciman, W B; Morris, R W; Watterson, L M; Williamson, J A; Paix, A D
Abstract : Background: Cardiac arrest attributable to anaesthesia occurs at the rate of between 0.5 and 1 case per 10 000 cases, tends to have a different profile to that of cardiac arrest occurring elsewhere, and has an in-hospital mortality of 20%. However, as individual practitioners encounter cardiac arrest rarely, the rapidity with which the diagnosis is made and the consistency of appropriate management varies considerably. Objectives: To examine the role of a previously described core algorithm "COVER ABCD–A SWIFT CHECK", supplemented by a sub-algorithm for cardiac arrest, in the management of cardiac arrest occurring in association with anaesthesia. Methods: The potential performance of this structured approach for each the relevant incidents among the first 4000 reported to the Australian Incident Monitoring Study (AIMS) was compared with the actual management as reported by the anaesthetists involved. Results: There were 129 reports of cardiac arrest associated with anaesthesia among the first 4000 AIMS incident reports. Identified aetiological factors were grouped into five categories: (1) anaesthetic technique (11 cases with this category alone; 32 with this and one or more of the other categories, representing 25% of all 129 cardiac arrests); (2) drug related (16; 32, 25%); (3) associated with surgical procedure (9; 29, 22%); (4) associated with pre-existing medical or surgical disease (30; 82, 64%); (5) unknown (8; 14, 11%). The "real life" presentation and management of cardiac arrest in association with anaesthesia differs substantially from that detailed in general published guidelines. Cardiac rhythms at the time were sinus bradycardia (23%); asystole (22%); tachycardia/ventricular tachycardia/ventricular fibrillation (14%); and normal (7%), with a further third unknown. Details of treatment were recorded in 110 reports; modalities employed included cardiac compression (72%); adrenaline (61%); 100% oxygen (58%); atropine (38%); intravenous fluids (25%), and electrical defibrillation (17%). There were no deaths or permanent morbidity in the 11 cases due solely to anaesthetic technique. 24 of the 25 deaths occurred in patients with significant pre-existing medical or surgical disease. Conclusion: Because there are often multiple contributing factors to a cardiac arrest under anaesthesia, a complete systematic assessment of the patient, equipment, and drugs should be completed. The "COVER ABCD–A SWIFT CHECK" algorithm was judged to be a satisfactory process in this context and should be carried out even if the cause of the cardiac arrest is already thought to have been found. The diagnosis and management of cardiac arrest in association with anaesthesia differs considerably from that encountered elsewhere. The outcome is generally good, with most patients leaving hospital alive and apparently well.